RACIAL OPPRESSION TOWARDS AFRICAN-AMERICAN SLAVES IN JOH KORTY’S THE AUTOBIOGRAPHY OF MISS JANE PITTMAN MOVIE - NASRUN JUHAIDI; SRI MINDA MURNI (Universitas Negeri Medan, 2021)
The objectives of this study were to find out 1) To investigate and explain the types of racial oppressionoccurred in the movie The Autobiography of Miss Jane Pittman, and 2) To describe how the charactersresisted the racial discrimination aimed to them in the movie The Autobiography of Miss JanePittman. The data are analyzed in descriptive qualitative approach. The data of this research werefrom the utterance of The Autobiography of Miss Jane Pittman movie characters. The data were takenfrom all the utterances, including monologues, dialogues, and narrations from the script which isalready transcripted from the movie. The result of this research showed that 1) there are four types ofoppressions that happened in the movie, namely: Exploitation with a total number of 2 utterances(6.7%), Marginalization with a total number of 10 utterances (33.3%), Powerlessness with a totalnumber of 6 utterances (20%), and violence with a total number of 12 utterances (40%). 2) There arethree types of resistance that are used by the characters, namely: Acquiescence with a total number of5 utterances (31.25%), violence resistance with a total number of 4 utterances (25%), Non-ViolenceResistance with a total number of 7 utterances (43.75%),